Analisis Sensitivitas dan Kalibrasi Model Hujan Debit 1D Menggunkan SWMM - Dhimas Krisna Wardana; Yang Ratri Savitri; Anak Agung Ngurah Satria Damarnegara (Universitas Muhammadiyah Surabaya, 2026)
Rainfall-runoff modeling using the Storm Water Management Model (SWMM) is a widely adopted approach for representing urban drainage systems. In urban drainage modeling with SWMM, the accuracy of simulation results is greatly influenced by the sensitivity of model parameters and the calibration process that aligns with actual field conditions. Therefore, parameter sensitivity analysis is necessary to identify the parameters that most significantly affect simulation outcomes, so that an optimal model parameter configuration can be obtained to accurately represent actual flood conditions. This study aims to evaluate the performance of the SWMM model in representing rainfall-runoff processes in urban drainage systems based on sensitivity analysis and parameter calibration. Sensitivity analysis was conducted on several hydrological parameters, namely the Curve Number (CN), Manning's N, and the percentage of impervious area. The sensitive parameters identified were then used in the model calibration and validation process. Validation was evaluated qualitatively by comparing simulation results with actual conditions observed in the drainage network. The results of the sensitivity analysis indicate that the parameter with the greatest influence on surface runoff is the Curve Number (CN) at 5.3%, followed by the overland flow Manning's N at 2.0%, while the remaining parameters showed negligible effects. Regarding infiltration, CN demonstrated a dominant influence of 88.9%. Furthermore, the parameters affecting channel discharge were the channel Manning's coefficient at 42.3%, followed by overland flow N at 5.1% and CN at 2.2%. The calibration results confirm that the parameter configuration derived from the sensitivity analysis is capable of producing simulations that are consistent with actual field conditions.